2023
DOI: 10.1002/alz.13458
|View full text |Cite
|
Sign up to set email alerts
|

Risk, protective, and biomarkers of dementia in Indigenous peoples: A systematic review

Huong X. T. Nguyen,
Kate Bradley,
Bridgette J. McNamara
et al.

Abstract: INTRODUCTIONDementia is an emergent health priority for Indigenous peoples worldwide, yet little is known about disease drivers and protective factors.METHODSDatabase searches were conducted in March 2022 to identify original publications on risk, protective, genetic, neuroradiological, and biological factors related to dementia and cognitive impairment involving Indigenous peoples.RESULTSModifiable risk factors featured across multiple studies include childhood adversity, hearing loss, low education attainmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Higher education levels correlate with better cognitive performance. Nguyen et al ’s systematic review indicated that education has the potential to act as a preventive factor against dementia ( 43 ). A study in China involving 1,286 older adult individuals supports the key role of education in maintaining cognitive health in disadvantageous settings ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Higher education levels correlate with better cognitive performance. Nguyen et al ’s systematic review indicated that education has the potential to act as a preventive factor against dementia ( 43 ). A study in China involving 1,286 older adult individuals supports the key role of education in maintaining cognitive health in disadvantageous settings ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…These programmes have mostly been conducted in small group settings, an aspect which itself may contribute to the effectiveness, as social activity is cognitively stimulating. 13 However, it should be noted that these approaches can be seen as 'add-ons' to the individual care of PwD. As these intervention programmes are conceptualised with a low frequency, intervention effects may lack sustainability.…”
Section: Open Accessmentioning
confidence: 99%
“…Empirically defined classification thresholds suggested the optimal threshold to classify any impairment (MCI, dementia, IN-MCI) with 3MSE was <90.5 and for MoCA < 19.5; to classify dementia alone with 3MSE was <92. 5…”
Section: Normative Neuropsychological Functioning (Cognitive Intact)mentioning
confidence: 99%
“…However, disparities in socioeconomics, historical, and sociological factors, with accompanying higher burden of risk factors and comorbidities, are likely to result in disparate prevalence, incidence, and risk models for some groups, especially Indigenous peoples. 4 , 5 American Indians, for example, endure a high prevalence of hypertension, diabetes, and depression; low access to resources and education; but also have high social support and resilience. 6 , 7 However, despite such high risk, little is yet established about the epidemiology of ADRD in American Indians and other Indigenous peoples.…”
Section: Introductionmentioning
confidence: 99%